The Pipeño: Story of a Typical Wine Southern Central Valley of Chile [el Pipeño: Historia de Un Vino Típico del Sur del Valle Central de Chile] - Lacoste, P (Universidad de Tarapaca, 2015)
This article studies the history of Pipeño, typical wine of south-central Chile. This is a wine made from grapes Country, Muscat of Alexandria and other landraces. It owes its name to the “pipes” Chilean oak barrels, which were first used in the eighteenth century. These are wines made from traditional methods, with deep roots in folk and peasant layers of Chile. For a long time was negatively valued by wine experts and specialists. But in recent years it has begun to discover from their identity, history and social roots. © 2015, Universidad de Tarapaca. All rights reserved.